(untitled) (Psychology Travelogs, 2023)
The article is devoted to the theoretical analysis of the problem of the person’s experiencing loss dynamics psychological aspects. The phenomenon of loss content has been established: loss is an event that causes a grief state and triggers the grieving process: death, separation, death of a pet, physical capabilities loss and material losses. The reaction to the loss is an emotional experience, which is classified as grief and the grieving process as its dynamic characteristic. The factors and features of the grieving dynamics as a complex human response to trauma, which includes such levels as: affective, cognitive, social, valuable, bodily, have been studied. It was found that the main elements of any grieving process are the meaning of the loss, emotional and cognitive strategies, and coping strategies. The grieving process depends on the resilience (psychological elasticity) and adaptability of the individual, as well as on the degree and type of attachment to the lost. It was determined that processes of self-regulation, adaptation, protective mechanisms and coping mechanisms, processes of social interaction, that is all available internal and external resources of a person experiencing a loss, are involved in processing the loss. It was concluded that during the loss processing process normal course, a person solves the following tasks: recognition of the loss, awareness of the emotions associated with the loss, study, research and integration (of the loss into his new life without the lost). In pathological grief, this dynamic is disrupted, which leads to devastating consequences for the individual and their interaction system. It was determined that grieving process psychological support and accompaniment is a purposeful systemic process that solves the following main tasks: 1) client’s internal and external resources determination; 2) cognitive and emotional processing of the client’s loss; 3) facilitation of grieving processes.